AN ANALYSIS OF THE IMPLEMENTATION OF PROBLEM BASED LEARNING IN LEARNING ENGLISH AT THE XI GRADE SCIENCE CLASS OF SMA NEGERI 1 SINGARAJA IN THE ACADEMIC YEAR 2015/2016 - Apriliadewi, P.A.R. (International Journal of Language and Literature, 2017)
This research aimed to describe the implementation of problem based learning science in learning English at the XI grade science class of SMA Negeri 1 Singaraja. The subjects of this research were an English teacher and 32 students of class XI MIA 6 in SMA N 1 Singaraja. Research methods used were observation, interview and questionnaire. The results of this research show that: (1) the implementation of problem based learning in learning English in XI MIA 6 class of SMA N 1 Singaraja has been implemented based on the phases of this model; (2)The problems faced by the English teacher during the implementation of problem based learning areÂ  the teacher is difficult to manage the learning time, determine the problem which is related to studentsâ characteristics, and cannot check all of the studentsâ work because of the big number of the studentsâ; (3)The main problem faced by the students during the implementation of this model was they cannot improve in collaborative learning in solving the problem. However, the students give a positive response to the implementation of problem based learning in their class.